From Specific to General in Electoral Cycle Models - Caleiro, António Bento (2019)
The article considers a way of generalizing the, so-called, stylized, which is also a specific, model of electoral cycles. This generalization consists on assuming that the output level does indeed exhibit persistence, i.e. its current value (may be) being a function (also) of its past value. In an integrated way, the consequences of of this generalization are analyzed.